2013
DOI: 10.1002/ev.20047
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of Performance Measurement as a Complement to Evaluation Among U.S. Foundations

Abstract: American philanthropic foundations began to foster evaluation as a force for accountability and transparency in the 1980s, followed by a focus on effective grant‐making practices by the end of the 1990s. Yet few foundations implemented internal processes to measure their own performance, or invested in evaluating their grant‐making programs. The turn of this century saw the rise of venture philanthropy, as grants became investments and achieving impact became the stated goal. Associated catchwords include stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Past research has emphasized a range of capacity issues facing nonprofit providers in general and with performance measurement in particular. This issue is rarely discussed with respect to funders; Boris and Kopczynski Winkler () are a notable exception. Six of the eight interviews in which capacity concerns were discussed were with organizations that had fewer than two full‐time employees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past research has emphasized a range of capacity issues facing nonprofit providers in general and with performance measurement in particular. This issue is rarely discussed with respect to funders; Boris and Kopczynski Winkler () are a notable exception. Six of the eight interviews in which capacity concerns were discussed were with organizations that had fewer than two full‐time employees.…”
Section: Discussionmentioning
confidence: 99%
“…Amirkhanyan () reported that lack of funder capacity was an impediment to collaboration in the performance measurement process. Similarly, Van Slyke (, ) found that governments lacked the capacity to monitor contracts in ways that would generate useful performance information; Boris and Kopczynski Winkler () raise this concern for foundations.…”
Section: Performance Measurement Challengesmentioning
confidence: 99%
“…Also, the peculiar status of foundations, which makes them directly accountable only to their own trustees, clashes with the public nature of the outcomes they produce in their communities, creating a special need for accountability (Fleishman, 2007). Thus, foundations' performance evaluation has become a fundamental tool to increase their accountability (Boris & Kopczynski Winkler, 2013). Communicating the impact of foundations' interventions may help them to increase their perceived legitimacy in their communities, as well as to reconsider their role in the public sphere, which is increasingly challenged (Anheier & Leat, 2013;Reich, 2013).…”
Section: Social Impact Assessment In Foundations: Concepts Methods Amentioning
confidence: 99%
“…CEO has been in existence for more than three decades and currently serves over 3,000 persons per year in New York City and several other locations in upstate New York, and has recently launched the CEO model in the states of Oklahoma and California with funding support from the Social Innovation Fund, a new federal program designed to expand the scale of high-impact nonprofit organizations delivering proven solutions that address pressing social issues (see also Boris & Winkler, 2013).…”
Section: About the Center Of Employment Opportunitiesmentioning
confidence: 98%